2022
DOI: 10.1177/00469580221125765
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, Physical and Behavioral Health of Adults, 3 Years After Exposure to a Train Derailment

Abstract: In July 2013, a train derailment profoundly disrupted the tranquility of the population of Lac-Mégantic for months and even years. In 2016, we conducted a representative population-based survey among 387 people from Lac-Mégantic and 413 from other municipalities with the aim to document psychological and physical health of adults exposed to the disaster. This article examines differences between 3 groups of respondents: those who were highly, moderately or not exposed to the train accident. Khi Square analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, in another study by Khodadadi-Hassankiadeh et al (2017b), being employed or self-employed before the RTA was not a predictor. Studies by Yaşan et al (2009), Huh et al (2017), and Maltais et al (2022) observed that unemployment after the RTA in 3 months to 3 years was also not a predictor. Finally, Blanchard et al (1995a, 1995b) did not prove the work status before the RTA to be a predictor after the RTA in 1 to 4 months.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…However, in another study by Khodadadi-Hassankiadeh et al (2017b), being employed or self-employed before the RTA was not a predictor. Studies by Yaşan et al (2009), Huh et al (2017), and Maltais et al (2022) observed that unemployment after the RTA in 3 months to 3 years was also not a predictor. Finally, Blanchard et al (1995a, 1995b) did not prove the work status before the RTA to be a predictor after the RTA in 1 to 4 months.…”
Section: Resultsmentioning
confidence: 92%
“…Lee et al (2021) reported that older students' age was a predictor 2.5 years after the accident (Lee et al, 2021). A study by Maltais et al (2022) has said that people older than 65 years are more susceptible to being diagnosed with PTSD 3 years after a train derailment. Age was a significant predictor in seven studies with 6,101 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations